2006
DOI: 10.1093/nar/gkl902
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis restricts localization of CID, the centromere-specific histone H3 variant of Drosophila, to centromeres

Abstract: Centromere identity is determined by the formation of a specialized chromatin structure containing the centromere-specific histone H3 variant CENP-A. The precise molecular mechanism(s) accounting for the specific deposition of CENP-A at centromeres are still poorly understood. Centromeric deposition of CENP-A, which is independent of DNA replication, might involve specific chromatin assembly complexes and/or specific interactions with kinetochore components. However, transiently expressed CENP-A incorporates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
123
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(129 citation statements)
references
References 30 publications
6
123
0
Order By: Relevance
“…In principle, the interdependence of centromeric Cenp-A/Cid, Cenp-C and the low levels of Cal1 might provide robust control of centromeric Cenp-A/Cid amounts and could effectively protect cells against the consequences of accidental unbalanced Cenp-A/Cid excess. However, previous studies have demonstrated that overexpression of Cenp-A/Cid is sufficient to cause ectopic incorporation all along the chromosome and consequential mitotic defects (Van Hooser et al, 2001;Heun et al, 2006;Moreno-Moreno et al, 2006). The massive overexpression applied in these studies (70-fold) (Heun et al, 2006), which is rather unlikely to occur in physiological conditions, even accidentally, might have over-run negative regulation.…”
Section: Interdependency Between Cal1 Cenp-a/cid and Cenp-c Limit Cementioning
confidence: 86%
“…In principle, the interdependence of centromeric Cenp-A/Cid, Cenp-C and the low levels of Cal1 might provide robust control of centromeric Cenp-A/Cid amounts and could effectively protect cells against the consequences of accidental unbalanced Cenp-A/Cid excess. However, previous studies have demonstrated that overexpression of Cenp-A/Cid is sufficient to cause ectopic incorporation all along the chromosome and consequential mitotic defects (Van Hooser et al, 2001;Heun et al, 2006;Moreno-Moreno et al, 2006). The massive overexpression applied in these studies (70-fold) (Heun et al, 2006), which is rather unlikely to occur in physiological conditions, even accidentally, might have over-run negative regulation.…”
Section: Interdependency Between Cal1 Cenp-a/cid and Cenp-c Limit Cementioning
confidence: 86%
“…Previous studies have shown that ubiquitin-mediated proteolysis of CENP-A is important for preventing CENP-A from euchromatin localization in budding yeast and Drosophila (Collins et al 2004;Moreno-Moreno et al 2006). To determine whether the N-terminal domain of CENP-A cnp1 plays a role in targeting the protein for degradation via the ubiquitin pathway in fission yeast, we first examined the stability of N-terminal-deleted CENP-A cnp1 -GFP compared to wildtype CENP-A cnp1 -GFP.…”
Section: N-terminal Domain Of Cenp-a Cnp1 Mediates Ubiquitin-dependenmentioning
confidence: 99%
“…In Drosophila, overexpression of the CENP-A homolog, CID, can lead to ectopic formation of heritable functional kinetochores and significant chromosome missegregation (Heun Olszak et al 2011). In budding yeast and Drosophila, ubiquitin-mediated proteolysis of CENP-A has been shown to contribute to the removal of mislocalized CENP-A at noncentromeric regions (Collins et al 2004;Moreno-Moreno et al 2006;Hewawasam et al 2010;Ranjitkar et al 2010). However, the mechanisms that protect cells from erroneously assembling CENP-A at noncentromeric chromatin remain poorly understood.…”
mentioning
confidence: 99%
“…Overexpression of Cse4 in a psh1Δ strain is toxic and is associated with localization of Cse4 to ribosomal DNA and euchromatin, 4,5 Proteasomal degradation of CENP-A has been reported in human cells and flies. 11 A Psh1 ortholog in other eukaryotes is difficult to verify since the RING and Zinc fingers are highly conserved motifs in many genes from yeast to human. It will be interesting in the future to determine whether ubiquitin-dependent proteolytic control is an evolutionarily conserved mechanism to regulate Cen-H3.…”
Section: Cse4 Gets a Kiss-of-death From Psh1mentioning
confidence: 99%